Understanding the impact related to lifestyle interventions for people with dementia: A systematic review protocol. - Laura Middleton; Vanessa Vucea-Tirabassi; Grace Liu; Jennifer Bethell; Heather Cooke; Heather Keller; Teresa Liu-Ambrose; Megan E O'Connell; Jackie Stapleton; Ingrid Waldron; Sarah Wu; Marie-Lee Yous; et al. (PLoS ONE)
There is growing evidence to suggest that lifestyle initiatives promote brain health and reduce dementia risk. However, there is comparatively limited research focused on lifestyle interventions among people living with dementia. Most recent systematic reviews of lifestyle interventions among people living with dementia centre on the impact of exercise on cognition; yet, functional abilities and quality of life are most consistently prioritized by people living with dementia, care partners, and healthcare professionals. There is insufficient evidence to inform guidelines on effective lifestyle interventions, programs, resources, and policies for people living with dementia. To address this knowledge gap, the objective of this study is to perform a systematic review to understand the impact of lifestyle interventions among people living with dementia. The specific research questions are: "What is the effectiveness of physical activity interventions on improving functional abilities and quality of life among community-dwelling people living with dementia?", "What is the effectiveness of healthy eating/nutrition on improving nutritional status or quality of life among community-dwelling people living with dementia?" and "Does the effectiveness of interventions vary depending on the components (single or multi), setting (in-home or community centre, geography), program structure, mode of delivery, dosage, and participant characteristics (sex/gender, ethno-cultural or language group, race, dementia type)?" The results from this review will inform recommendations of lifestyle interventions and their delivery among people living with dementia in the community. Trial registration: Systematic review registration PROSPERO #CRD42024509408.